Valor nutritivo das silagens de milho e de sorgo e do pé-de-milho e pé-de-sorgo secos - Coelho da Silva, J F; Gomide, J A; Fontes, C A A (Revista Ceres, 2025)
Castrated lambs (3/treatment) were used in digestion and nitrogen balance studies to compare four roughages: corn silage, corn fodder with ears, sorghum silage and sorghum fodder, in a complete randomized design.